"Savaging the Civilized; Verrier Elwin, His tribals, and India" - "Guha, Ramachandra" (Gurgoan, 2014)
This evocative and beautifully written book brings to life one of the most remarkable figures of twentieth-century India. Verrier Elwin (1902-64) was an anthropologist, poet, Gandhian, hedonist, Englishman and Indian. Savaging the Civilized reveals a many-sided man, a friend of the elite who was at home with the impoverished and the destitute; a charismatic charmer of women who was comfortable with intellectuals such as Arthur Koestler and Jawaharlal Nehru; an anthropologist who lived and loved with the tribes yet who wrote literary essays and monographs for the learned. Savaging the Civilized is both biography and history, an exploration through Elwin's life of some of the great debates of our times, such as the impact of economic development and cultural pluralism versus cultural homogeneity. For this new edition, Ramachandra Guha has added a long new introduction, stressing the relevance of Elwin's work to current debates on adivasis, Naxalites and Indian democracy.
Keywords: Sociology